2017
DOI: 10.1186/s12904-017-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: When parents face the death of their child: a nationwide cross-sectional survey of parental perspectives on their child’s end-of life care

Abstract: During production of the original article [1], Additional file 2 of this article was linked to an incorrect document. Instead of the complete item list of the PaPEQu as the authors submitted it, it was a STROBE checklist. The correct additional file has been included with this erratum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This study also showed that compliance with European guidelines resulted in increased test scores. 115 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also showed that compliance with European guidelines resulted in increased test scores. 115 …”
Section: Resultsmentioning
confidence: 99%
“…Only 43.9% of Japanese medical schools have compulsory palliative care sessions, while 30.3% have no clinical clerkship curriculum at all. 116 Teaching in Thailand revealed a lack of coping management skills when caring for palliative care patients while at least one school in India has no cancer education program at all. 117 Egyptian medical education showed a national public health based approach to cancer education which even requires completion of a community service project, however it lacks standardized training in cancer education and prevention.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, previous studies demonstrated that the care burden of mothers was quite high. [25][26][27][28] It has been stated that it is not easy for parents to transfer their responsibilities to someone else. 27 Home care teams and social support systems should be well coordinated in order to support the family and the home care needs of children who are dependent on medical technology.…”
Section: Discussionmentioning
confidence: 99%